Design management : managing design strategy, process and implementation - Best, Kathryn (Required reading range., 2015)
Takes the reader through the strategy, process and implementation of design management via an exploration of the required skills, theory and practice of each. This title includes case studies and interviews from some of the leading professionals and corporations.